Decoupling CEO Wealth and Firm Performance: The Case of Acquiring CEOs - HARFORD, JARRAD; LI, KAI (Journal of Finance, 2007)
ABSTRACT We explore how compensation policies following mergers affect a CEO's incentives to pursue a merger. We find that even in mergers where bidding shareholders are worse off, bidding CEOs are better off three quarters of the time. Following a merger, a CEO's pay and overall wealth become insensitive to negative stock performance, but a CEO's wealth rises in step with positive stock performance. Corporate governance matters; bidding firms with stronger boards retain the sensitivity of their CEOs' compensation to poor performance following the merger. In comparison, we find that CEOs are not rewarded for undertaking major capital expenditures.